Perceptions and practices about menstrual hygiene among women of reproductive age group (15-49 years) attending out-patient department of CIMS, Bilaspur Chhattisgarh - Pandey, Bhavana; Shukla, Devesh (International Journal Of Community Medicine And Public Health, 2018)
Background: Women suffer due to their ignorance on hygienic requirement during menstruation. Hygiene related practices of women during menstruation are of considerable importance, as it has a health impact in terms of increased vulnerability to RTI. Inthis paper our objectives is to detect the menstrual health problems and to assess menstrual hygiene practices among women of reproductive age group (15-49 years) attending OPD of CIMS Bilaspur Chhattisgarh (Obstretic and Gynaecology, OPD). Methods: Females of reproductive age group (15-45 years) attending routine obstretics and gynaecology OPD during 1st May to 15th September 2015 were included in the study after taking their verbal consent at CIMS hospital. Pretested semi-structured questionnaire were used to take history regarding knowledge and practices related to menstrual hygiene. Statistical test like chi-square test were applied using Epi info 7 software. Results: 36% of study population belonged to the 21-30 year age group. About 75% were married. Majority of women had primary education (43.3%) and 54.3% belonged to lower middle class. Majority of women 51.8% used cloth during menstruation; about 45.7% used the same cloth by washing and reusing every month. Conclusions: Most women were found to follow unhygienic practices. Hence, efforts such as improving female literacy and health education regarding the various risk factors should be made by the policy makers to increase menstrual hygiene among rural population. Literacy status was found to be significant for awareness about menstruation and the use of sanitary pads.